PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMPN 4 PAINAN - Anggun Gusti Pratama; Dina Ramadhanti; Trisna Helda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the ability to write exposition texts of class VIII students of SMPN 4 Painan before the implementation of the Cooperative Integrated Reading and Composition (CIRC) model. To determine the ability to write exposition texts of class VIII students of SMPN 4 Painan after the implementation of the Cooperative Integrated Reading and Composition (CIRC) model. To analyze the effect of using the Cooperative Integrated Reading and Composition (CIRC) model on the ability to write exposition texts of class VIII students of SMPN 4 Painan. This type of research is quantitative research using experimental methods. The design of this study is One Group Pretest-Posttest Design. The population of this study was all class VIII students of SMPN 4 Painan. The sample in this study was class VIII.1, totaling 20 people. The data in this study were scores on the ability to write exposition texts of class VIII students of SMPN 4 Painan after the implementation of the Cooperative Integrated Reading and Composition (CIRC) model. The results of this study can be concluded that the learning outcomes of the ability to write expository texts of grade VIII students of SMPN 4 Painan using the Cooperative Integrated Reading and Composition (CIRC) model, or a probability below α 0.05 (0.000 < 0.05), from these results it can be seen that Ho is rejected and Ha is accepted. Keywords: Cooperative Integrated Reading and Composition (CIRC), Writing Ability, Expository Text